Consolidation of Competition Law and Consumer Protection Law in Indonesia : A Normative Study Based on Hans Kelsen's Pure Theory of Law - wim badri zaki; Gunsu Nurmansyah; Wim Fadel Azmilhuda (Faculty of Law-Universitas Bandar Lampung, 2026)
This article discusses the urgent need to merge Indonesia's Competition Law and Consumer Protection Law into a single enforcement body. Since 1999, Indonesia has maintained two separate legal entities: the Business Competition Supervisory Commission (KPPU) under Law No. 5 of 1999, and the National Consumer Protection Agency (BPKN) under Law No. 8 of 1999, with an annual budget of Rp 401 billion. Using a normative legal research method with statutory and conceptual approaches, this article assesses the legal validity of both laws after four amendments to the 1945 Constitution, evaluates the effectiveness of the dual institutional system, and advocates for consolidation based on Hans Kelsen’s pure theory of law and the principle of economic democracy. The study reveals that this separation has caused significant structural failures: by July 2025, Rp 265.49 billion in KPPU fines from 114 final decisions remained unenforced, and BPKN recovered only 10.6 percent of Rp 424.3 billion in documented consumer losses in 2024, with 70 percent of its recommendations ignored by government agencies. The total loss from these inefficiencies in a single year exceeds the combined budgets of both agencies. Considering models like the US Federal Trade Commission (FTC) and the Australian Competition and Consumer Commission (ACCC), and noting that 89 of 148 countries adopted a consolidation approach, this article argues that establishing a Competition and Consumer Protection Commission (KPPK) is an urgent constitutional, academic, and fiscal priority for Indonesia.